1989
DOI: 10.1128/jcm.27.1.78-81.1989
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus intermedius in canine gingiva and canine-inflicted human wound infections: laboratory characterization of a newly recognized zoonotic pathogen

Abstract: Staphylococcal gingival flora was characterized in cultures from 135 dogs. Staphylococcus intermedius was isolated in 39% of the cultures, S. aureus was isolated in 10%, and both were isolated in 2.0%. S. aureus was isolated more often from dogs of working breeds with weights of >40 lb (ca. 18 kg) and with outdoor habitats than was S. intermedius, which was associated with dogs of nonworking breeds with weights of <40 lb and indoor habitats. S. intermedius was distinguished from S. aureus by the following char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0
5

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 28 publications
7
45
0
5
Order By: Relevance
“…intermedius was obtained from 30 cats, which represents 28·8% of the isolates. This species is the major pathogenic staphylococcal species in dogs (Devriese 1990) and causes skin, urinary tract, bone and central nervous system infections in several animal species (Talan et al 1989). Their presence has already been reported in canine gingiva and canine-inflicted human wound infections (Talan et al 1989), on the skin (Cox et al 1985;Lilenbaum et al 1998) and in the mouth of clinically healthy cats (Cox et al 1985).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…intermedius was obtained from 30 cats, which represents 28·8% of the isolates. This species is the major pathogenic staphylococcal species in dogs (Devriese 1990) and causes skin, urinary tract, bone and central nervous system infections in several animal species (Talan et al 1989). Their presence has already been reported in canine gingiva and canine-inflicted human wound infections (Talan et al 1989), on the skin (Cox et al 1985;Lilenbaum et al 1998) and in the mouth of clinically healthy cats (Cox et al 1985).…”
Section: Discussionmentioning
confidence: 98%
“…Although synthetic penicillinase-resistant penicillins such as oxacillin and methicillin are considered to be effective against the majority of staphylococcal strains (Talan et al 1989), 23 strains (22·1%) were identified as resistant to methicillin; these strains were distributed among all the Staphylococcus species except Staph. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance genes are easily acquired in such a polymicrobial environment. Their habitat on mammals makes staphylococci very amenable to spread from one animal to another and in some situations to humans by cat and dog bites (Talan et al 1989). Staphylococci are largely species specific and most of the times strains from one species do not cause infections in another species and there are few reports in the literature of spread of staphylococci between species.…”
Section: Spread Of Resistance Staphylococcimentioning
confidence: 99%